2023
DOI: 10.1111/gcb.16622
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon stocks in stable tropical landforms are dominated by geochemical controls and not by land use

Abstract: The loss of forests driven by cropland expansion and deforestation for timber, agriculture, or charcoal production is a global problem, with great consequences for terrestrial carbon cycling. The vast majority of research analyzing the effect of land conversion on SOC dynamics focuses on geochemically less altered and more intensively managed soils of the temperate zone (Cotrufo et al., 2019;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 132 publications
0
19
0
Order By: Relevance
“…However, since these soils have relatively high concentration in 1:1 clay minerals with limited capacity to stabilize SOC, higher C input will not necessarily lead to higher SOC concentrations (Table 2; Figures 2b and 5; Khomo et al., 2017; Six, Feller, et al., 2002; Wattel‐Koekkoek et al., 2003). The potential of deeply weathered soils that dominate these regions is often limited in its capacity to stabilize C inputs (Georgiou et al., 2022; Reichenbach et al., 2023), while microbial decomposition is high (Cusack et al., 2009). Our findings thus support the idea that some of the geochemically older tropical soils in humid climate zones may be closer to SOC ‘saturation’ (Six, Conant, et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since these soils have relatively high concentration in 1:1 clay minerals with limited capacity to stabilize SOC, higher C input will not necessarily lead to higher SOC concentrations (Table 2; Figures 2b and 5; Khomo et al., 2017; Six, Feller, et al., 2002; Wattel‐Koekkoek et al., 2003). The potential of deeply weathered soils that dominate these regions is often limited in its capacity to stabilize C inputs (Georgiou et al., 2022; Reichenbach et al., 2023), while microbial decomposition is high (Cusack et al., 2009). Our findings thus support the idea that some of the geochemically older tropical soils in humid climate zones may be closer to SOC ‘saturation’ (Six, Conant, et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The same soils may be less responsive to declining plant productivity if soil minerals can efficiently retain SOC via mineral adsorption (Torn et al, 1997;Figure 6c). In contrast, soil C stocks in predominantly old, deeply weathered soils with younger SOC ages (Figure 5) might not react to climatic changes if biomass productivity continues to exceed the limited capacity of these soils to stabilize C by minerals (Reichenbach et al, 2023;Torn et al, 1997). However, these soils may be very sensitive to decreases in biomass productivity and thus plant C inputs under drier climate conditions (Figure 6c; Feller, 1993;Good & Caylor, 2011).…”
Section: Future Scenarios Of Soc Persistencementioning
confidence: 99%
“…Multilayers of TOC or macromolecular OC-Fe complexes to preserve TOC when particle surfaces become saturated (Chen et al, 2014;Li et al, 2023). Previous study also reported that there was no correlation between TOC fractions and pH, Fe ox (1.7-4.2 g/Kg), or Al oxides Al ox (1.7-4.2 g/kg) in topsoils (0-20 cm) in subtropical China, while effects of Fe ox on soil properties was significant (Mao et al, 2020), and the specific mineralogical properties and reactivity determine TOC stocks in tropical forest and cropland and was constrained by soil mineralogy (Reichenbach et al, 2023). In additional, recent study found that maybe only carboxyl-rich TOC coprecipitated with ferrihydrite becomes more stable in the solid phase (Zhao et al, 2022), and in turn TOC occurrence can delay the conversion of Fe (hydroxyl) oxide to iron minerals with higher crystallity (Pasakarnis et al, 2014).…”
Section: Correlation Between Toc and Iron Statesmentioning
confidence: 90%
“…Most studies have discussed the mechanism for stabilizing TOC by iron minerals in continent soil and in the lakes, salt marsh wetlands, or ocean sediments (Lalonde et al, 2012;Ma et al, 2018;Reichenbach et al, 2023;Zhao et al, 2023). The TOC sequestration controlled by iron minerals is complicated and strongly related to the redox conditions of sediments (Hartnett et al, 1998;Hemingway et al, 2019).…”
Section: Correlation Between Toc and Iron Statesmentioning
confidence: 99%
“…Our study provides direct evidence to support the earlier call by Rasmussen et al (2018) to consider type and reactivity of minerals rather than only the clay content for predicting soil OM content. It adds to the demonstrated superiority of other predictors, such as the concentration of pedogenic oxides (Herold et al, 2014;Kirsten et al, 2021;Rasmussen et al, 2018;Reichenbach et al, 2023).…”
Section: Impli C Ati On S and Outlookmentioning
confidence: 99%